Frequency selective EMI shield for “quiet hospital wards” - Tan, Alex Boon Siu. (2011)
As more medical electronics are being employed in hospitals, these wards would require visitors to switch off their mobile phones so as to prevent mobile phones from causing erroneous readings or stoppage of life sustaining medical equipment. Therefore, it is becoming critical to ensure electromagnetic interference (EMI) on such medical devices be minimized.